Comparative analysis of anti‐polyglutamine Fab crystals grown on Earth and in microgravity. Issue 10 (6th October 2016) - Owens, Gwen E.; New, Danielle M.; Olvera, Alejandra I.; Manzella, Julia Ashlyn; Macon, Brittney L.; Dunn, Joshua C.; Cooper, David A.; Rouleau, Robyn L.; Connor, Daniel S.; Bjorkman, Pamela J.
Abstract : Microgravity was used in an attempt to define the crystal structure of the polyQ repeat of huntingtin alone or bound to MW1, an anti‐polyQ Fab. While huntingtin was not crystallized in the experiments, analysis of microgravity‐grown and Earth‐grown MW1 Fab crystals showed that, on average, microgravity‐grown crystals of MW1 Fab showed an increase in size and an improvement in resolution and mosaicity when compared with Earth‐grown crystals in one space group, in agreement with data published for other proteins, although the highest overall resolution X‐ray data in our experiments were obtained from a crystal grown on Earth. Abstract : Huntington's disease is one of nine neurodegenerative diseases caused by a polyglutamine (polyQ)‐repeat expansion. An anti‐polyQ antigen‐binding fragment, MW1 Fab, was crystallized both on Earth and on the International Space Station, a microgravity environment where convection is limited. Once the crystals returned to Earth, the number, size and morphology of all crystals were recorded, and X‐ray data were collected from representative crystals. The results generally agreed with previous microgravity crystallization studies. On average, microgravity‐grown crystals were 20% larger than control crystals grown on Earth, and microgravity‐grown crystals had a slightly improved mosaicity (decreased by 0.03°) and diffraction resolution (decreased by 0.2 Å) compared with control crystals grown on Earth. However, the highest resolution and lowest mosaicity crystals were formed on Earth, and the highest‐quality crystal overall was formed on Earth after return from microgravity.